5s-(100+2s)=0

Simple and best practice solution for 5s-(100+2s)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5s-(100+2s)=0 equation:


Simplifying
5s + -1(100 + 2s) = 0
5s + (100 * -1 + 2s * -1) = 0
5s + (-100 + -2s) = 0

Reorder the terms:
-100 + 5s + -2s = 0

Combine like terms: 5s + -2s = 3s
-100 + 3s = 0

Solving
-100 + 3s = 0

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '100' to each side of the equation.
-100 + 100 + 3s = 0 + 100

Combine like terms: -100 + 100 = 0
0 + 3s = 0 + 100
3s = 0 + 100

Combine like terms: 0 + 100 = 100
3s = 100

Divide each side by '3'.
s = 33.33333333

Simplifying
s = 33.33333333

See similar equations:

| 3(10-6)(3-7)= | | 55m-139m-64m= | | 8x^6/6x^3 | | ln(x-3)=1.4 | | x-9(2/3x-6)=30 | | 1/2z=9/4 | | -5/13x=-8 | | 5m-139m-64m= | | 10m^3n^3-2mn^2+14mn= | | x+y-3z=-7 | | -9+8x=7x+15 | | 5(x+8)-6=44 | | 8x^2-28x+2x-7=.5 | | 5849=3.14x*81 | | 11w=132 | | -30=x+12 | | 17.8-(-4.006)-22= | | 4(-7e+9)+6=82 | | 46=(-6t)-8 | | (16x^5-x)(4x^2-9)=0 | | 4+(19-42)2= | | 2n+n=57 | | 12x(3x-2+5y)-4(5x-3y+2)-5y= | | r*25=6 | | 4=225 | | n/2-4=18 | | 2m^2+7m-1=-6 | | 3x/27=8/2x | | 5n+6+6n=30 | | 3(n-8)=5 | | 3p^2q^2+6pq+p= | | 5p-7q=-1 |

Equations solver categories